Acute pulmonary embolism combined with acute myocardial infarction as the first manifestation of acute leukemia: a case report - Zheng, Shuzhan; Luo, Sha; Luo, Yong; Liu, Dan; Zheng, Wenwu; Peng, Qing (Frontiers in Cardiovascular Medicine, 2023)
Thrombotic complications in acute myeloid leukemia (AML) are uncommon due to coagulation dysfunction and thrombocytopenia. We report a unique case of AML presenting as concomitant pulmonary embolism and atypical acute myocardial infarction. A 67-year-old male experienced persistent bilateral chest pain. Despite an unremarkable electrocardiogram, elevated D-dimer and mildly increased troponin T levels prompted further investigation, leading to the diagnosis of simultaneous pulmonary embolism and acute myocardial infarction. The patient underwent percutaneous coronary intervention and received triple antithrombotic therapy. However, antithrombotic therapy was discontinued following a sharp decline in hemoglobin and platelet counts, and the patient subsequently developed persistent fever. AML was diagnosed via bone marrow biopsy. Chemotherapy was not initiated due to the patient's deteriorating condition, and he ultimately succumbed to presumed intracranial bleeding.